A Pre-experimental Study to Evaluate the Effectiveness of Structured Teaching Program on Knowledge Regarding Dental Care among Secondary Schoolchildren in the Selected School of Jind, Haryana - Khatkar, Suman (International Journal of Nursing Research, 2023)
Aim: The important public health issue among adolescents is poor oral health. Various studies have noted a high prevalence of dental problems among adolescents despite the efforts, the level of dental caries remains prevalent in developed countries; it has increased in developing countries due to dietary changes. The aim of this pre-experimental study was to evaluate the effectiveness of structural teaching program on the knowledge regarding dental care among secondary schoolchildren in selected school of Jind, Haryana. Methodology: This pre-experimental study was included 60 children from secondary school of Haryana selected by simple random sampling technique. Data were collected by self-structured knowledge questionnaire. Data analysis was done by means of descriptive and inferential statistics. Results: Pre-test, an overwhelming majority of the samples 55 (91.66%) were having poor level of knowledge regarding dental hygiene. Samples who had average level of knowledge were 5 (8.34%). None of the samples were having good level of knowledge. Post-test, an overwhelming majority of the samples 39 (81.67%) were having good level of knowledge regarding dental hygiene. Samples who had average level of knowledge were 11 (18.33%). None of the samples were having poor level of knowledge, and in the present study, it was found that there was no statistically significant association between pre-test level of knowledge and the selected demographic variables. Conclusion: There are findings of the study shown that the structured teaching programmed was more effective in improving the knowledge of the children regarding dental care.